Test For Antioxidant Activity Of Hair Tonic Preparations Ethanol Extract 70% Pegagan Leaves (Centella asiatica (L.) Urban) - Lazaely Anggita Mayasari; Supriyanto; Estuningtyas Ayu Hapsari (Yayasan Citra Dharma Cindekia, 2024)
Gotu kola leaves (Centella asiatica (L.) Urban) are wild plants that grow in various places such as fields, plantations and in yards. Gotu kola leaves contain compounds such as polyphenols, β-carotene, tannins, vitamin C and saponins such as Madecassida and Asiaticoside. The asiaticoside found in gotu kola functions as an antioxidant that can capture free radicals. Objective: To determine the 70% ethanol extract of gotu kola leaves (Centella asiatica (L.) Urban) as a hair tonic as an antioxidant using different concentration variants. Method: This research is an experimental study by testing the antioxidant activity of a hair tonic preparation of gotu kola leaf extract (Centella asiatica (L.) Urban) in a hair tonic preparation on antioxidants using the DPPH 2,2 diphenyl-1-pikeylhydrazyl method. The 70% ethanol extract of gotu kola leaves was obtained using the maceration method with 70% ethanol solvent where the thick extract obtained was tested for its compound content. Then the extract with a concentration of 5ml, 10ml, 15ml was made into a hair tonic preparation after which it was tested for physical quality, organoleptic test, homogeneity test, pH test , viscosity test, specific gravity test. Vitamin C as a positive control and hair tonic base as a negative control. After obtaining comparisons, the data were processed statistically using ANOVA. Results: This research shows that the 70% ethanol extract of gotu kola leaves (Centella asiatica (L.) Urban) contains the chemical compounds triterpenoids, flavonoids, saponins, alkaloids and tannins. All hair tonic formulations have antioxidant activity based on the IC50 value. The statistical test results show that there is a significant difference in antioxidant activity, namely (p<0.05).